0464 Sleep Continuity by Neighborhood: Are There Differences?. (27th May 2020) - Giller, J; Muench, A; Grandner, M A; D'Antonio, B; Perlis, M L
Abstract: Introduction: To our knowledge, no prior work has been conducted on whether sleep continuity disturbance (e.g., SL; WASO; EMA, etc.) varies by neighborhood. While differences on these metrics have been found by, e.g., race and socioeconomic status, it may also be that sleep continuity disturbance varies relative to where one lives and works. Accordingly, an analysis was undertaken to assess whether regional differences exist with respect to sleep continuity disturbance (SCD). Methods: The study utilized a cross-sectional group design in an archival/community dataset that was collected in the Philadelphia area (www.sleeplessinphilly.com ). This dataset (n = 2840) was comprised of adults between 18 and 89 years of age with self-reported sleep complaints (63.4% female; 36.6% male; average age 38). Study subjects who endorsed >30 minutes on >3 days/week on SL, WASO & EMA were categorized by zip code and into four regional groups: Center City (n=258); South Philadelphia (n=103); North & Northeast Philadelphia (n=400) and West Philadelphia (n=345). Contingency analyses and ANOVAS were used to assess for regional group differences. Results: It was found that SCD rates significantly differed by region. Differences in percent endorsement by region were as follows, SL:, 64.1% (Northeast/North), 63.5 (South), 56.3% (West Philadelphia), & 48.7% (Center City); WASO: 45% (Northeast/North), 40% (South), 36.5% (West Philly), & 32.4% (Center City); EMA: 46.4% (South); 43.7 (Northeast/North); 43.7 (West Philly); 43.1 (Center City). Conclusion: The Northeast/North region of Philadelphia had the highest rates, and center city had the lowest rates of SCD for the early part of the night (SL & WASO). Early morning SCD was most common for "South Philly and least common for Center City. Analyses are on-going in relation to other regional differences (demographic, income, crime stats, etc.) and those found to vary by region will be assessed for their predictive value. Support: No support was provided for this abstract